The acute testosterone, growth hormone, cortisol and interleukin-6 response to 164-km road cycling in a hot environment - Vingren, J. L.; Budnar Jr., R. G.; McKenzie, A. L.; Duplanty, A. A.; Luk, H.-Y.; Levitt, D. E.; Armstrong, L. E. (Journal of Sports Sciences, 2016)
This study investigated the acute endocrine responses to a 164-km road cycling event in a hot environment. Thirty-four male experienced cyclists (49.1 ± 8.3 years, 86.8 ± 12.5 kg, 178.1 ± 5.1 cm) participating in a 164-km road cycling event were recruited. Blood samples were collected within 0.3-2.0 h before the start (PRE: ~0500-0700 h) and immediately following the ride (POST). Samples were analysed for testosterone, growth hormone (GH), cortisol and interleukin-6 (IL-6). The temperature and humidity during the event were 35.3 ± 4.9°C and 47.2 ± 14.0%, respectively. Based on the finishing time, results for the fastest (FAST, 305 ± 10 min) and the slowest (SLOW, 467 ± 31 min) quartiles were compared. At POST, testosterone concentration was significantly (P < 0.05) lower (PRE, 20.8 ± 8.6; POST, 18.2 ± 6.7 nmol/ L), while GH (PRE, 0.3 ± 0.1; POST, 2.3 ± 0.3 µg/L), cortisol (PRE, 661 ± 165; POST, 1073 ± 260 nmol/L) and IL-6 (PRE, 4.0 ± 3.4; POST, 22.4 ± 15.2 pg/mL) concentrations were significantly higher than those at PRE. At POST, GH and cortisol were significantly higher for the FAST group than for the SLOW group (GH, 3.6 ± 2.0 and 1.0 ± 0.8 µg/L; cortisol, 1187 ± 209 and 867 ± 215 nmol/L). Participation in an ultra-endurance road cycling event in a hot environment induced significant acute changes in concentrations of circulating hormones, with a greater augmentation of GH and cortisol in those completing the ride fastest.